PEMAHAMAN MAHASISWA SEJARAH TERHADAP MATERI PERKULIAHAN PENDIDIKAN - Farida Luwistiana; Sumiyatun Sumiyatun (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2011)
The purpose of this research is to discuss about attitude and perception of students on Department of education of history, Faculty of teacher’s training and educational science, Muhammadiyah University of Purwokerto. Especially in understanding and internalization of educational subject matters. Factors had an effect on students interest concerning non-educational subject matters. Next, students understanding phase toward education matters, and level of students consciousness to importance of educational subject matters in application in educational field. Key words: understanding, attitude, interest, student.